Reconstruction of pre-monsoon relative humidity since 1800 C.E. based on tree-ring data of Pinus roxburghii Sarg. (chir–pine) from Pithoragarh, Western Himalaya. (20th August 2022) - Dhyani, Rupesh; Shekhar, Mayank; Joshi, Rajesh; Bhattacharyya, Amalava; Ranhotra, Parminder S.; Pal, Ashish K.; Thakur, Shinny; Nandi, Shyamal K.
Abstract: Relative humidity (RH), an important climatic element influencing tree growth, is also crucial in assessing the General Circulation Models (GCMs) on global warming. However, in the absence of a relatively long record of RH in the Himalayan region, precise modelling of the climate change related processes and their impacts on this region are not well established. Here we present a new RH reconstruction for the pre-monsoon months (February–May) starting from 1800 C.E. using the tree-ring width data of subtropical Pinus roxburghii (chir-pine) from Pithoragarh, Western Himalaya, India. We found significant positive correlation between tree growth and pre-monsoon RH ( n  = 67, r = +0.569, p < 0.001). Based on this relationship, the developed linear regression model explains 32.5% of the total variance during the calibration period from 1949 to 2015 C.E. The region experienced 28 high and 25 low humidity years over the past 215 years. The five highest and three lowest humidity years were identified as 1831, 1836, 1881, 1977, 1982 and 1939, 1999, 2013 C.E. Further, we found a declining trend in RH during the past 35 years. This decline in RH over the Himalaya indicates that the global warming is not evident as expected by the climate modellers. The reliability of the reconstructed data is validated by the significant positive correlation with column water vapour/relative humidity gridded data of ERA-interim (850 mb) for 1979–2015 C.E. over the Himalayan region. Further, a consistent and significant positive relation with precipitation and a negative correlation with temperature over this region confirm the reliability of the reconstructed RH data. Spectral analysis reveals the existence of periodicities of 2–10 years, which may be linked with effects of El-Nino-Southern Oscillation (ENSO) over the India subcontinent.